Evolutionary constraints on the long-period subdwarf B binary PG 1018–047. Issue 1 (24th October 2017) - Deca, J.; Vos, J.; Németh, P.; Maxted, P. F. L.; Copperwheat, C. M.; Marsh, T. R.; Østensen, R.
Abstract: We have revisited the sdB+K-star long-period binary PG 1018–047 based on 20 new high-resolution Very Large Telescope/Ultraviolet and Visual Echelle Spectrograph spectra that provided regular coverage over a period of more than 26  m. We refine the period and establish that the orbit is significantly eccentric ( P  = 751.6 ± 1.9 d and e  = 0.049 ± 0.008). A simultaneous fit derived from the narrow metal lines visible in the spectrum of the sdB star and the metal lines in the red part of the spectrum that originate from the companion provides the mass ratio, M MS / M sdB  = 1.52 ± 0.04, for the system. From an NLTE model atmosphere analysis of the combined spectra, we find T eff  = 29900 ± 330 K, log  g  = 5.65 ± 0.06 dex and log( n He / n H ) = –3.98 ± 0.16 dex for the primary, consistent with a B-type hot subdwarf star. The spectral contribution of the companion is consistent with a K5V-type star. With the companion having a mass of only ∼ 0.7 M⊙, this system lies close to the boundary below which stable Roche lobe overflow (RLOF) cannot be supported. To model the evolution of such a system, we have extended earlier MESA models towards lower companion masses. We find that both phase-dependent mass loss during RLOF, when 30 to 40 per cent of the available mass is lost through the outer Lagrange point and phase-dependent mass loss during RLOF in combination with a circumbinary disc of maximum M CB = 0.001 M⊙ could have formed the PG 1018–047 binary system.